Factores nutricionales, sociales, psicoafectivos y de salud de los adultos mayores (2006)
ABSTRACT: The aging is a dynamic, progressive and irreversible process influenced by many biological, physical and social factors. High proportion of the society sees in aging, a process in which people lose their autonomy, independence, and intellectual capacity, consequently elderly people become a burden for their families and for the society. During last years, this concept has been changing favorably in part because of desire of adults and elderly people of having a successful and active aging as defined by the Word Health organization. This definition consist of physical, social and mental well-being opportunities of elderly stage as part of the vital process, with adequate nutrition and physical activity, aspects, that are usually neglected. This process is experienced by all countries in the world, some of them with higher rates. Although Colombia does not have those rates, strategies need be established in order to improve the quality of life of this population.